Magnetic field sensors using 13-spin cat states - Simmons, S; Jones, J; Karlen, S; Ardavan, A; Morton, J (2010)
Measurement devices could benefit from entangled correlations to yield a measurement sensitivity approaching the physical Heisenberg limit. Building upon previous magnetometric work using pseudoentangled spin states in solution-state NMR, we present two conceptual advancements to better prepare and interpret the pseudoentanglement resource. We apply these to a 13-spin cat state to measure the local magnetic field with a 12.2 sensitivity increase over an equivalent number of isolated spins. © 2010 The American Physical Society.